Arithmetic of finite fields : 6th International Workshop, WAIFI 2016, Ghent, Belgium, July 13-15, 2016, Revised selected papers /: 6th International Workshop, WAIFI 2016, Ghent, Belgium, July 13-15, 2016, Revised selected papers. (2016) - Unknown
No abstract available